Effect of bio-fertilizers and phosphate fertilization on the vegetative and flowering growth of the Fennel fruits (Foeniculum vulgare Mill): Effect of bio-fertilizers and phosphate fertilization on the vegetative and flowering growth of the Fennel fruits (Foeniculum vulgare Mill) - Arak, Rana Rayyis; Jader, Jassim Jawad; Hussain, Madiha Hamudi (Journal of Kerbala for Agricultural Sciences, 2020)
A factorial experiment was conducted in Al-Watifiyah region 40 km north of Babylon for the winter agricultural season 2018 with the aim of knowing the effect of bio-fertilizers and phosphate fertilizers in the indicators of vegetative and flowering growth of fennel plant(Foeniculum vulgare Mill), where a factorial experiment was applied to Randomized Complete Block Design (R.C.B.D) with three replicates, The first two factors were used that included the use of four levels of bio-fertilizers, (without addition, mycorrhiza, and Azotobacter spp , Mycorrhiza + Azotobacter spp). The second factor was the use of four levels of phosphate fertilizer P2O5 (0, 40, 60 and 80 kg.ha-1). Data were collected, statistically analyzed, and arithmetic averages were arranged according to the LSD test, the probability at the level of 5% . The results showed that the bio-fertilizers had a significant effect on the studied traits, where treatment of Azotobacter bacteria and adding phosphorus the level of 60 kg.ha-1 excelled and giving the highest average plant height (159.67 cm), the number of vegetable branches (15.0 branch.plant-1), dry weight of the vegetative growth (12.92 g) . While the interaction of Mycorrrizae and the adding of phosphorous at 60 kg.ha -1 achieved a significant increase in the number of inflorescences (12.67 inflorescences.plant-1), the number of florets in the inflorescence (9.67 florets. Inflorescence-1), the 1000 grains weight (10.0 g), total fruit yield (1.83 tons.ha-1) while the control treatment gave the lowest average of all studied traits.